Dime Novel Desperadoes : The Notorious Maxwell Brothers - Hallwas, John E. (Book collections on Project MUSE., 2008)
This thrilling historical true crime narrative recovers the long-forgotten story of Ed and Lon Maxwell, outlaw brothers from Illinois who once rivaled Jesse and Frank James in national notoriety. Growing up hard as the sons of a tenant farmer, the Maxwell brothers embarked on a life of crime that captured the public eye. Made famous locally by newspapers that dramatized crimes and danger, the brothers achieved national prominence in 1881 when they shot and killed Charles and Milton Coleman, lawmen trying to apprehend them. Public outrage sparked the largest manhunt for outlaws in American history, involving some twenty posses who pursued the desperadoes in Wisconsin, Minnesota, Iowa, Illinois, Missouri, and Nebraska. Nevertheless, the daring desperadoes were eventually portrayed as heroes in sensationalistic dime novels. A stunning saga of robbery and horse stealing, gunfights and manhunts, murder and mob violence, Dime Novel Desperadoes also delves into the cultural and psychological factors that produced lawbreakers and created a crime wave in the post-Civil War era. Every overview and encyclopedia of American outlaws will need to be revised, and the fabled "Wild West" will have to be extended east of the Mississippi River, in response to this riveting chronicle. With more than forty illustrations and several maps that bring to life the exciting world of the Maxwell brothers, Dime Novel Desperadoes is a new classic in the annals of American outlawry.